2011
DOI: 10.1002/mrm.22969
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial first‐pass perfusion: Influence of spatial resolution and heart rate on the dark rim artifact

Abstract: Myocardial perfusion images can be affected by the dark rim artifact. This study aimed to evaluate the effects of the spatial resolution and heart rate on the transmural extent of the artifact. Six pigs under anesthesia were scanned at 1.5T using an echo-planar imaging/fast gradient echo sequence with a nonselective saturation preparation pulse. Three short-axis slices were acquired every heart beat during the first pass of a contrast agent bolus. Two different in-plane spatial resolutions (2.65 and 3.75 mm) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition to ringing effects, there may be other potential contributing factors to the DRA as listed in the Introduction. Furthermore, it is difficult to decouple the contribution of each factor [e.g., motion versus ringing (19,59)]. Nevertheless, the left-to-right pattern of the observed DRAs in Cartesian images matches the PE direction ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ringing effects, there may be other potential contributing factors to the DRA as listed in the Introduction. Furthermore, it is difficult to decouple the contribution of each factor [e.g., motion versus ringing (19,59)]. Nevertheless, the left-to-right pattern of the observed DRAs in Cartesian images matches the PE direction ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies were limited to rest perfusion scans (maximum imaged heart rate ¼ 78 beats per minute). Previous works have suggested that stress imaging is more prone to DRAs, which has been attributed to a higher degree of Gibbs ringing (7,10) and increased cardiac motion (19,59). The results of our phantom study suggest that, even for sharp signal-intensity discontinuities (6:1 ratio in Figure 5), the optimized radial imaging method effectively eliminated ringing-induced DRAs.…”
Section: Limitationsmentioning
confidence: 99%
“…Greater spatial coverage makes it less likely to miss ischemic areas and allows for better sizing of ischemia. High spatial resolution can reduce the dark rim artifact [5][6][7] which can mimic subendocardial defects. 8 High temporal resolution can also be important in reducing dark rim effects and to accurately track signal intensity changes.…”
Section: Introductionmentioning
confidence: 99%
“…With Cartesian sampling, the so‐called “k‐t” accelerated methods (k‐t BLAST/SENSE/PCA) utilize advanced model‐based reconstruction to achieve high spatiotemporal accelerations, thereby significantly improving in‐plane spatial resolution to reduce DRA . The underlying principle is that higher spatial resolution reduces the visual extent and severity of Gibbs ringing, one of the major causes of DRA . However, unlike conventional vendor‐provided schemes that reconstruct each frame independently using parallel‐imaging acceleration, “k‐t” methods require temporal acceleration and specialized reconstruction software/hardware that are not available across different MRI scanner platforms.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] The underlying principle is that higher spatial resolution reduces the visual extent and severity of Gibbs ringing, 8 one of the major causes of DRA. 5,8,13 However, unlike conventional vendor-provided schemes that reconstruct each frame independently using parallel-imaging acceleration, "k-t" methods require temporal acceleration and specialized reconstruction software/hardware that are not available across different MRI scanner platforms. Furthermore, established k-t accelerated imaging methods require a breath-hold scan, which can be difficult to achieve, especially during vasodilator stress studies.…”
mentioning
confidence: 99%